Body mass index, waist circumference, and risk of hearing loss: a meta-analysis and systematic review of observational study - Jin-Rong Yang; Khemayanto Hidayat; Cai-Long Chen; Yun-Hong Li; Jia-Ying Xu; Li-Qiang Qin (Komiyama Printing Co. Ltd, 2020)
Abstract Background Emerging evidence implicates excess weight as a potential risk factor for hearing loss. However, this association remained inconclusive. Therefore, we aimed to systematically and quantitatively review the published observational study on the association between body mass index (BMI) or waist circumference (WC) and hearing loss. Methods The odds ratios (ORs) or relative risks (RRs) with their 95% confidence intervals (CIs) were pooled under a random-effects model. Fourteen observational studies were eligible for the inclusion in the final analysis. Results In the meta-analysis of cross-sectional studies, the ORs for prevalent hearing loss were 1.10 (95% CI 0.88, 1.38) underweight, 1.14 (95% CI 0.99, 1.32) for overweight, OR 1.40 (95% CI 1.14, 1.72) for obesity, 1.14 (95% CI 1.04, 1.24) for each 5 kg/m2 increase in BMI, and 1.22 (95% CO 0.88. 1.68) for higher WC. In the meta-analysis of longitudinal studies, the RRs were 0.96 (95% CI 0.52, 1.79) for underweight, 1.15 (95% CI 1.04, 1.27) for overweight, 1.38 (95% CI 1.07, 1.79) for obesity, 1.15 (95% CI 1.01, 1.30) for each 5 kg/m2 increase in BMI, and 1.11 (95% CI 1.01, 1.22) for higher WC. Conclusions In summary, our findings add weight to the evidence that elevated BMI and higher WC may be positively associated with the risk of hearing loss.